Perioperative drug management in non-critical companion animals: a retrospective study at a Spanish veterinary teaching hospital (2018–2022) - Beatriz Romero; Julen Susperregui; Ana M. Sahagún; José R. Altónaga; Cristina López; Raúl de la Puente; José M. Rodríguez; Milena Vázquez; Raquel Díez (Veterinary Quarterly)
There is little information in veterinary literature on the perioperative pharmacological management of small animal patients, despite the existence of common protocols and the importance of properly managing this period to reduce anaesthesia-related detrimental effects. This study aimed to analyse the current use of perioperative drugs in companion animals treated at the Veterinary Teaching Hospital of the University of León (HVULE) in Spain over a period of 5 years (2018–2022), describe the prescription patterns of these medicines, and identify the main variables associated with their prescription to explore possible strategies to promote their appropriateness. A total of 3438 cases were included in this study. The animals that most frequently underwent surgery were dogs (58.2%), females (57.0%), and adults (73.0%). The primary procedures performed were reproductive (56.6%) and traumatological (19.8%) surgeries. Regarding pharmacological treatments, more than half (62.3%) belonged to the ATCvet classification QN group (nervous system), and the most common compounds were isoflurane (13.5%), methadone (13.5%), and propofol (12.7%). Amoxicillin/clavulanic acid (3.7%) and marbofloxacin (2.8%) (categories C and B in the European Medicines Agency categorisation, respectively) were the most prescribed antibiotics. These findings provide detailed data to help veterinary policymakers improve drug use during surgical procedures.